The effect of using the learning-by-play strategy on female students’ achievement in chemistry and their attitudes towards the subject - Abu Zaherah, Nadia Obidullah; Al-Harbi, Eman Khaled; Al-Shehri, Lara Ali (Journal of Curriculum and Teaching Methodology, 2025)
The current study aims to identify the effect of using the gamified learning strategy on female students’ achievement in chemistry and their attitudes toward the subject. To achieve the goal of the study, the researchers used the quasi-experimental approach on a sample of 90 female students who were divided into two equal groups, one experimental (45) student, and the other a control group. (45) control subjects, and the study tools were the achievement test and a measure of attitude toward the subject. The study concluded that there were statistically significant differences between the scores of the experimental and control groups in the achievement test in favor of the experimental group. It also concluded that there were statistically significant differences between the scores of the pre-test of the attitude scale towards the subject and the scores of the post-test of the experimental group in favor of the post-test, which indicates the effectiveness of learning through play. Considering this, the researcher made some recommendations, such as including learning through play strategies in the teacher’s guide in the subject of chemistry, holding training workshops to train teachers on the use of educational games, whether manual or electronic, and suggestions, holding training workshops to train teachers on modern strategies that motivate learners and make their attitudes towards the subjects positive.
Keywords: Strategy; learning by playing; Academic achievement; attitudes